Bone Mineral Density and Jumping Height in Pre-Menarcheal and Post-Menarcheal Physically Active Girls - Rita Gruodytė; Toivo Jürimäe (Lithuanian Sports University, 2018)
Research background and hypothesis. Jumping ability correlates well with different bone values. The skeletal benefits of high-impact weight-bearing exercise have been shown to be greater when training is started prior to menarche. We hypothesized that significant differences would be apparent in the relationships between bone values and jumping height in favor of the girls' prior menarche compared to post-menarcheal group. Research aim. The aim of the study was to investigate the relationships between jumping height and bone mineral density (BMD) in pre-menarcheal and post-menarcheal physically active girls. Research  methods.  In  total,  113  adolescent  girls  from  different  competitive  extramural  athletic  programs participated in this study. Femoral neck and lumbar spine BMD were measured. The heights of vertical jumps (i. e. countermovement jump (CMJ) and rebound jumps for 15 (RJ  15 s) and 30 (RJ  30 s) seconds) were obtained. Research results. After adjusting for major confounders (i. e. age, height, and body mass), the height of rebound jumps correlated only with femoral neck BMD and only in pre-menarcheal group (r = 0.37-0.46; p < 0.05). No correlations were found between BMD variables and jumping height in post-menarcheal girls. The height of CMJ did not correlate with measured BMD variables in the studied groups. Discussion and conclusions. Early puberty is an opportune period to increase bone adaptation to mechanical loading due to the velocity of bone growth and endocrine changes at this time. We suggest that powerful repetitive vertical jumping may be more beneficial to bone health compared to single jumping activities in physically active girls prior to menarche rather than after it. Keywords: bone health, vertical jumps, puberty.